Digital Parenting : Challenges and Roles of Parents in the Era of Society 5.0 - Swanny Trikajanti Widyaatmadja; Solechan, Achmad (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
It is important to carry out this research because it is related to the theme of digital parenting, child care carried out by parents, especially in the use of information technology (gadgets/devices). This research uses qualitative methods with literature review techniques with the results of discussing 34 research article publications that are relevant to this research. The research results show the role of parents in The application of digital parenting in the current era of society 5.0 requires extra effort. In terms of implementation digital parenting, not only parents required to be able to understand things about advances in information technology, however On the other hand, parents are also required to serve as a good example in operating the device digital . In the era of Industrial Revolution 5.0, digital parenting faces several unique challenges related to technological advances and social change, continuous technological updates, technology develops quickly and new devices and applications are introduced frequently.